MA Defence: “Waste Media Pedagogy: Soundscape Composition as Re-sponsive Spatial Practice - Phan, Vu Thuy Anh (Stream: Interdisciplinary Journal of Communication, 2015)
Our dear colleague, Pietro Sammarco, will defend his MA Thesis on Wednesday, December 16, 2015 at Harbour Centre, Room 1500 (1:00 am - 12:00 pm). Here is the abstract of his thesis “Waste Media Pedagogy”: